Postpartum Depression: A Literature Review of Screening and Prevention - Hana Andrina (HM Publisher, 2021)
Pregnancy is a complex and vulnerable period that presents a number of challenges to women, including the development of postpartum psychiatric disorders. These disorders can include postpartum depression and anxiety, which are relatively common, and the rare but more severe postpartum psychosis. In addition, other postpartum psychiatric disorders can include obsessive-compulsive disorder, post-traumatic stress disorder and eating disorders. The etiology of postpartum psychiatric disorders is a complex interaction of psychological, social and biological factors, in addition to genetic and environmental factors. The goals of treating postpartum mental illness are reducing maternal symptoms and supporting maternal-child and family functioning. Women and their families should receive psychoeducation about the illness, including evidence-based discussions about the risks and benefits of each treatment option. In this article, we would like to focus on postpartum depression (PPD). Identifying and treating this problem can reduce the alarming number of suicides among depressed perinatal women and the possible adverse effects of untreated maternal depression on their child’s cognitive and behavioral development. Developing effective strategies in global settings that allow the delivery of targeted therapies to women with different clinical phenotypes and severities of PPDs is essential. In this review, we discuss the latest developments in screening, treatment, and prevention methods.